Short-focus psychodynamic oriented psychotherapy as treatment optimization technique in involution psychoses - Pustovoyt , Mykhailo; Pinchuk, Iryna (Psychosomatic Medicine and General Practice, 2019)
Aim of the research. This article is based on the results of empirical experience and a pre-conducted study of the effectiveness of treatment of patients with mental disorders that manifested in the middle period of life (45-60 years). These findings provide an algorithm of short-term psychodynamic oriented psychotherapy focuses on such kind of patients. Materials and Methods. In order to optimize the psychotherapeutic process, this article suggests to use differentiated therapeutic tactics and interpretive techniques, according to the specific phase of therapy. Each of these tactics and techniques should be focused and correspond to the actual experience of the patient. The proposed method of psychotherapy is a "method of choice" for the treatment of involutional psychosis in combination with medication. With sufficient qualifications of the therapist, this technique can be used both during the active existence of symptoms of psychosis, and within the limits of remission. Results. The research findings illustrate that the central focus of the experiences of patients with mental disorders manifested in the middle period of life (45-60 years) is the need to come to terms with their own lives (with the circumstances of the internal and external realities). According to this fact, the central focus of the therapeutic work with such patients should be formulated in the same way. The treatment process of this central focus occurs in six psychotherapeutic phases, each of which develops its thematic aspect. These phases can be conditionally placed in the following sequence: 1) the phase “building trust with the therapist”; 2) the phase of “making claims to/in the inner circle”; 3) the phase of “memories of one’s own achievements and good times” (the phase of “relative validation / verification” of the positive moments of one’s life, and therefore the positive qualities of one’s own personality); 4) the phase of “rethinking your life and understanding your own part in it”; 5) the phase “understanding the connection between one’s own life and a current illness”; 6) the phase of “forgiveness of oneself for the mistakes, finding new values in life”. Conclusions. We have shown that the central focus of the experiences of patients with mental disorders manifested in the middle period of life (45-60 years) is the need to reconcile with their own lives. According to this fact, the central focus of therapeutic work with such patients should be object-oriented reconciliation with the circumstances of internal and external realities. The psychotherapeutic process proceeds in six separated phases. The therapist should differentiate therapeutic tactics and interpretive techniques in each of these phases. The therapist`s methods should be congruent with the actual focus of the patient's experiences and the patient's level of the integration of the Ego.